Perbandingan Efektivitas Metode Penyuluhan Langsung dan Pemberian Leaflet terhadap Peningkatan Pengetahuan tentang Narkoba pada Remaja - Achmad Dwityanto Oktaviansyah; Muhammad Luthfi Prasetyo; Nurul Mutmainah (Journal of Pharmaceutical and Sciences, 2026)
Background: Drug abuse among adolescents is a serious public health problem. Health communication strategies such as direct counseling and leaflet distribution are commonly used, yet their comparative effectiveness remains underexplored. Objective: To compare the effectiveness of direct counseling versus leaflet distribution in improving adolescents’ knowledge about drug abuse. Methods: This experimental study used a two-group pre-test post-test design involving 62 adolescents at Mandhanisiwi Orphanage, Purbalingga. Group I (n=31) received direct interactive counseling (100 minutes), while Group II (n=31) received leaflets (100 minutes self-study). Knowledge was measured using a validated 20-item true-false questionnaire. Data were analyzed using Wilcoxon and Mann-Whitney tests. Results: Both groups showed significant knowledge improvement after intervention (p=0.000 for Group I; p=0.001 for Group II). The mean post-test score of Group I (80.81±7.86) was significantly higher than that of Group II (74.35±10.78) with p=0.022 (Mann-Whitney). Conclusion: Direct counseling is more effective than leaflet distribution in improving adolescents’ knowledge about drug abuse prevention. This method is recommended as the primary educational strategy in school- or community-based drug prevention programs.